Technical and Program Realization of On-Line Educational Network - I. A. Tavgen (Наука и техника)
This paper proposes a structural network scheme of the on-line educational system which is based on the Unibel/NIKS network. In addition to purely educational functions this system can provide the possibility of professional communication and exchange of experience between the system-users. The technical package of the on-line educational system includes a personal computer loaded with the relevant software that ensures realization of the following functions: a server of applications, integrated data transfer from a local network to the on-line educational system organization and external network. The main server components of the on-line educational network and operational station are considered and suggested in the paper.